2021
DOI: 10.3390/molecules26071966
|View full text |Cite
|
Sign up to set email alerts
|

Adlay Testa (Coix lachryma-jobi L. var. Ma-yuen Stapf.) Ethanolic Extract and Its Active Components Exert Anti-Proliferative Effects on Endometrial Cancer Cells via Cell Cycle Arrest

Abstract: Endometrial cancer is the most common malignant tumors of gynecologic neoplasms in Western society. In recent years, the incidence of endometrial cancer has increased, and it has become the third most common female gynecological cancer (after ovarian and cervical cancer) in Taiwan. Adlay (Coix lachryma-jobi L. var. Ma-yuen Stapf.) has been demonstrated to have bioactive polyphenols, flavonoids, phytosterols, and essential nutrients for health benefits, including anticancer effects in humans. However, little is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The proportion of late apoptotic cells treated with different concentration of RLE was higher than that of the control group, and the inhibition degree increased as the concentration grew, thus indicating that RLE could bring HT-29 cell apoptosis. Promoting apoptosis is the way that many natural products play an anticancer role, and R. molle has a lower effective drug concentration compared with other Chinese herbal medicines [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of late apoptotic cells treated with different concentration of RLE was higher than that of the control group, and the inhibition degree increased as the concentration grew, thus indicating that RLE could bring HT-29 cell apoptosis. Promoting apoptosis is the way that many natural products play an anticancer role, and R. molle has a lower effective drug concentration compared with other Chinese herbal medicines [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following our previous study using HPLC and GC/FID, ATE-EA was found to contain phenolic compounds, including protocatechuic acid, p-hydroxybenzoic acid, chlorogenic acid, vanillic acid, p-hydroxybenzaldehyde, syringic acid, vanillin, syringaldehyde, caffeic acid, p-coumaric acid and ferulic acid. Therefore, ATE-EA showed promising antitumor effects on endometrial cancer cells [8]. The effects of AHE-Ea-K, AHE-Ea-L, ATE-Ea-E and ATE-Ea-F on MCF-7 cells could be related to the presence of active flavonoids in the effective subfraction layer, such as naringenin.…”
Section: Discussionmentioning
confidence: 93%
“…The Coix seeds were processed by a dehulling machine to obtain the outer shell (35.8% of the weight of the Coix seeds) and then the skin and Coix seeds were air-sieved to obtain the testa (6.8% of the weight of the Coix seeds). The Coix seeds were further divided into Coix bran (4.3% of the weight of the Coix seeds) and refined white Coix seed (53.1% of the weight of the Coix seeds) [8]. Dehulled adlay, consisting of bran and endosperm, is regarded as a healthy cereal material, while the adlay hull and testa are treated as waste.…”
Section: Adlay Extract Preparationmentioning
confidence: 99%
See 2 more Smart Citations